MODIFIKASI PERENCANAAN STRUKTUR DENGAN BALOK PRATEKAN PADA GEDUNG HOTEL DAN MALL DI RUAS JALAN MT. HARYONO KENDARI - Talanipa, Romy; Mursidi, Baso (STABILITA || Jurnal Ilmiah Teknik Sipil, 2013)
AbstractHouse Hotel and Mall Road MT.Haryono Kendari is a building consisting of six floors and was planned with reinforced concrete structures. In terms of functionality and usefulness, this building does not yet have adequate meeting space so as to enhance the functionality and usefulness of the need for meeting space, which requires a vast place and freely without any hindrance. For the majority of the fields must be eliminated and will cause some long -span beams have.??????????????? With the ability to carry the load on long -span and behavior that combines high strength concrete with high strength steels are active , it can minimize the use of prestressed concrete structures as well as provide an alternative dimension of proper planning and efficient.Structural design modifications only in terms of technical structure, without considering the economic and aesthetic terms. Modifications made on the 5th floor and 6th floor. Analysis refers to the structure of the building regulations in Indonesia and other supporting regulations. The structure of the planned building structures meet safety requirements, based on the strength and deformation arising from the load acting on the structure with ductility level 2.Especially for prestressed beams, the planning is based on the method of implementation in the field by considering the strength and behavior of structural components at a critical stage since bias given moment. Modified the calculation Prestressed force : 2500 kN , the cable layout : E field = 250 mm , E = 100 mm pedestal , Loss of presstress : 17.9 , soft reinforcement installation staging area : 4D - 25 and field areas : 2D - 25.?Keywords: Modified, Prestressed Beams